Illusion and Allegory in the Baroque Art of the Banat: An Introduction - Vlăsceanu, Mihaela (Eikón / Imago, 2022)
The present study aims to underline the particularities found in the Banat by means of reinterpreting some of the main creations of Central-European late Baroque, where the illusion of the Habsburg power and allegories of Catholic faith were employed in the unifying artistic discourse. The main methods used range from comparative-historical to iconographic, with a structural-semantic and formal analysis of the works presented as case studies. The epideictic rhetoric of these examples contributes to a better acknowledgement of the role played by art in every society, having in mind that the eighteenth-century artistic phenomenon was synergic with the Central-European evolution and the style was tributary to the late Baroque, one of the many variants with particularities of the so-called “Baroques”.